Ochotona hyperborea subsp. uralensis Flerov 1927 - Lissovsky, Andrey A.; Obolenskaya, Ekaterina V.; Dokuchaev, Nikolai E.; Okhlopkov, Innokentiy M. (Zenodo, 2021)
Ochotona hyperborea uralensis Flerov, 1927 Ochotona hyperborea naumovi Formozov et Yakhontov, 2003 Lectotype (designated by).— Ognev 1940 ZIN 16107, adult female, skull and skin. Collected by K. K. Flerov 10.8.1926. Paralectotypes (Baranova et al. 1981): ZIN 16106, 16110, 16111. Type locality (according to museum label).— Eastern slope of Bolshoy Ural, Kharuta River, Synya River tributary (65.79°N, 62.78°E). Description.— Pikas of the B genetic lineage; northern acoustic race. The majority of the representatives of this subspecies (except for pikas from the Ural Mountains) have a clear V-shaped parietal suture (Fig. 5B). Accordingly, besides genetic identification, this subspecies can be distinguished from neighboring O. h. hyperborea by the shape of the parietal suture of the skull (Fig. 5). There are differences in the shape of the frequency modulation curve of alarm call with another spatial neighbor— O. h. cinereoflava (Fig. 6). Distribution.— The subspecies has a notably disjunct distribution—the northern Ural Mountains, Putorana Plateau and adjacent uplands, as well as Yakutia between the middle and lower Aldan River basin (to the north of Aldan Plateau) and Lena River basin (right bank, to the north of the Buotama River), including mountains of the Verkhoyansk region. The provisional distribution border with O. h. hyperborea corresponds roughly to the course of the Indigirka River. The case of mitochondrial introgression from the latter subspecies was found in the Adycha River basin. This subspecies should contact O. h. cinereoflava along the foothills of the Aldan Plateau and Dzhugdzhur Range, but an exact contact zone remains unknown. Nomenclatural notes.— Only two nominal taxa were described from the distribution range of this subspecies. The senior synonym appeared to be Ochotona hyperborea uralensis Flerov, 1927, which described a specimen from the very remote isolate in Ural Mountains. Published as part of Lissovsky, Andrey A., Obolenskaya, Ekaterina V., Dokuchaev, Nikolai E. & Okhlopkov, ...